PENGEMBANGAN MODUL AJAR IPAS BERBASIS READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE BAGI SISWA KELAS IV SEKOLAH DASAR - Marlina, Marlina (FASHLUNA, 2024)
This study aims to produce a science teaching module based on Read, Answer, Discuss, Explain, and Create for fourth graders of SDN Gambut 3. This research was conducted at SDN Gambut 3. The topic developed is the Form of Substance and Its Changes. The research method used is the Design and Development research method. The research model used is Planning, Production and/or Evaluation. Data collection techniques use Observation, interviews, and expert validation. Data analysis was carried out qualitatively, obtained through Observation and interviews and quantitatively, obtained from the expert validation questionnaire. The validation result is to find out the feasibility of the Teaching Module. The results from the Teaching Module Expert were 96.02% with the category Very Feasible for Use from the Media Expert 87.05% with the category Very Feasible for Use and from the Learning Expert 91.87% with the category Very Feasible for Use. The accumulated results by the three experts were 91.6% with the category Very Feasible for Use. So, it can be concluded that the development of the Science teaching module based on Read, Answer, Discuss, Explain, and Create for fourth graders of SDN Gambut 3 is feasible to use.